Editorial - Lorber, Lučka (Journal for Geography, 2015)
The tenth year of the Journal of Geography, published by the Department of Geography of the Faculty of Arts, University of Maribor, whose editor-in-chief and editor-in-chief for all these years has been Assoc. Prof. Dr. Igor Žiberna, is upon us. The members of the Department of Geography decided to dedicate the jubilee edition to Professor Emeritus Dr. Borut Belc, who celebrated the 85th anniversary of his life. On behalf of generations of geography students and fellow geographers, we congratulate our dear professor on his jubilee.Translated with DeepL.com (free version)